Economic Aspects of Risk Management of Stakeholders Activities - Shinkevich, Alexey I.; Lubnina, Alsu A.; Koryakov, Alexey G.; Mikhailov, Vladimir G.; Vodolazhskaya, Ekaterina L. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the fact that economic and productive activities which are completely free from risks are an unattainable goal and it is necessary to develop effective strategies for risk management, involving diverse scientific, economic and social research. The purpose of this paper is to develop methods of risk assessment of enterprises' industrial activities. The leading method to the study of this problem is the modeling method that allows considering of this problem as a purposeful and organized process to improve the economic risk management of economic entities' industrial activities. With the purposes of state regulation the method of industrial risks' assessment by economic sectors is adapted in the paper, based on the concept of reliable production; the subject structure of organizational and economic, production and technical, ecological and economic risks' areas in industrial enterprises of the Republic is investigated. The practical value is that the developed methodology allows the authorities of the region to improve the development and implementation of management decisions and more accurately identify priority areas for economic development of socially significant industrial enterprises. The proposed developments can be used in the development of programs of economic and ecological policy aimed at improving of the reliability and sustainability of businesses entities and market sectors of the economy, also they are of interest for local governments, businesses entities and economic ministries and agencies, which are responsible for strategic analysis and planning. Keywords: Risk, Production, Cluster, Sustainable Development JEL Classifications: D81, L23, O31